Gender and Conversion Narrative in a New Zealand Context - Bosma, David (Journal of sociology and Christianity, 2019)
Two articles, published in 2005 and 2012 respectively, have analyzed the narratives of converts to Christianity, and delineated the differences in storytelling style that have emerged between male and female study participants. Both articles borrow heavily from the work of gender theorist Deborah Tannen in how they structure this analysis. However, given that both of these projects were undertaken in the United States of America, and with largely Caucasian participants, there is significant scope for further research into the relationship between gender and conversion narrative. Thirty-two semi-structured interviews with recent converts to Christianity from secular backgrounds in Canterbury, New Zealand, are the basis for the original data presented in this paper. Referral sampling was used as a means of finding participants who were willing and available to share their story of coming to faith with the researcher. The data were analyzed in the same fashion as the North American projects, yet in some places yielded different results, particularly in the areas of relational connection with the interviewer, storytelling style, and central character. The inclusion of New Zealand Māori participants in the present study is one reason for this, and indicates the significance of ethnicity in determining individual storytelling style, an observation that is somewhat overlooked in the earlier projects. A seventh category, the need for experiential proof, is also offered as one further way in which male and female storytellers differ in how they narrate their conversion experiences.